Decay width modeling of Higgs boson within THDM model - Obikhod, T.V.; Petrenko, E.A. (Вопросы атомной науки и техники, 2021)
As part of the search for new physics beyond the Standard Model, we chose the determination of the Higgs boson decay width as one of the least experimentally determined values. The decay widths into the four fermions of the lightest and heaviest CP-even Higgs bosons of the THDM model were calculated, taking into account QCD and electroweak corrections in the NLO approximation. To achieve this goal, the program Monte Carlo Prophecy 4f with special scenarios of parameters, 7B1 and 5B1 were used. It was found that the decay width of the heavier CP-even Higgs boson H differs from Hₛₘ by 1227.93 times and changes to a negative value when deviating from the standard scenarios. Scale factors kz² and kw² showed the predominance of the associated with Z boson production cross section of CP-even Higgs boson over the associated with W production cross section. У рамках пошуків нової фізики за межами стандартної моделі нами було обрано визначення ширини розпаду бозона Хiггса, як одного з найменш експериментально визначених значень. Розрахована ширина розпадiв на чотири фермiони найлегшого i важчого CP-парного бозонiв Хiггса моделi THDM з урахуванням КХД i електрослабких поправок у NLO-наближеннi. Для реалiзацiї цiєї цiлi було використано програму Монте-Карло Prophecy 4f зi сценарiями простору параметрiв 7B1 та 5B1. Виявлено, що ширина розпаду важчого СР-парного бозона Хiггса Н вiдрiзняється вiд Hₛₘ у 1227,93 рази i змінюється до від’ємного значення при вiдхиленнi вiд стандартних сценарiїв. Масштабнi фактори kz² і kw² показали переважання пов’язаного з Z-бозоном перерiзу народження CP-парного бозона Хiггса H над асоцiйованим з W-перерiзом. В рамках поисков новой физики за пределами стандартной модели нами были выбраны определения ширины распада бозона Хиггса, как одно из наименее экспериментально определенного значения. Рассчитана ширина распадов на четыре фермиона легкого и тяжелого CP-парного бозонов Хиггса модели THDM с учетом КХД и электрослабых поправок в NLO-приближении. Для реализации этой цели была использована программа Монте-Карло Prophecy 4f со сценариями пространства параметров 7B1 и 5B1. Выявлено, что ширина распада тяжелого СР-парного бозона Хиггса Н отличается от Hₛₘ в 1227,93 раза и меняется к отри-цательному значению при отклонении от стандартных сценариев. Масштабные факторы kz² и kw² показали преобладание связанного с Z-бозоном сечения рождения CP-парного бозона Хиггса H над ассоциированным с W-сечением.